Abolishing Public Guarantees in the Absence of Market Discipline - Isabel Schnabel; Tobias Körner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper shows that the abolition of state guarantees to publicly owned banks in Germany resulted in an increase in refinancing costs at German savings banks. Rather than being the result of increased market discipline, the increase in refinancing costs is shown to be driven by spillover effects from German Landesbanken who themselves had suffered from the abolition of guarantees and who spread their own cost increase through the public banking network. Higher refinancing costs and the resulting drop in bank charter values translated into higher risk-taking at German savings banks.
Keywords: G21; G28; H11; 330